Prediction of Lymphovascular and Perineural Invasion of Oral Squamous Cell Carcinoma by Combined Expression of p63 and Cyclin D1 - Al-Rawi, Natheer H; Kawas, Sausan Al; Ani, Muwaffaq Al; Alnuaimi, Ahmed Sameer; EL-Sayed, Walid; Alrashdan, Mohammad S. (European Journal of Dentistry, 2023)
Objectives The aim of this study was to determine the value of immune expression of p63 and cyclin D1 in the prediction of lymphovascular invasion (LVI) and perineural invasion (PNI) in oral squamous cell carcinoma (OSCC).Materials and Methods Clinical and histopathologic features of 65 subjects with histologically confirmed OSCC were collected. Tissue microarray blocks representing all subjects were prepared for the immunohistochemical quantification of the nuclear expression of p63 and cyclin D1 using immune ratio plugin of image J software. Image analysis was performed by two independent pathologists. Independent samples t-test, analysis of variance, and receiver operating characteristic curve tests were used for statistical analysis. The level of significance was set at p≤ 0.05.Results The optimum cutoff value for the prediction of LVI for p63 and cyclin D1 was found to be 100 and 93.2, respectively, while the optimum cutoff value for the prediction of PNI for p63 and cyclin D1 was found to be 95.9 and 94, respectively. p63 and cyclin D1 expression correlated with several clinicopathologic features of the studied population. p63 expression was a significant predictor of moderate/poorly differentiated OSCC compared with well-differentiated OSCC. A parallel combination of positive p63 and cyclin D1 increased the specificity of predicting LVI from 89.1% and 67.4% for either p63 or cyclin D1, respectively, to 93.5% with a positive predictive value of 92.5%. Similarly, the parallel combination of the two markers raised the specificity of predicting PNI from 70% and 77.5% for either p63 or cyclin D1, respectively, to 90% with a positive predictive value of 86.3%.Conclusion Combined overexpression of nuclear markers p63 and cyclin D1 can be considered as a valuable independent predictor of LVI and PNI, and hence tumor progression, in OSCC.
Keywords: p63; cyclin D1; lymphovascular invasion; perineural invasion; tissue microarray; oral squamous cell carcinoma.